2018
DOI: 10.3389/fimmu.2018.02963
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Prevention of Titanium Particle-Induced Inflammation and Osteolysis

Abstract: The worldwide number of dental implants and orthopedic prostheses is steadily increasing. Orthopedic implant loosening, in the absence of infection, is mostly attributable to the generation of wear debris. Dental peri-implantitis is characterized by a multifactorial etiology and is the main cause of implant failure. It consists of a peri-implant inflammatory lesion that often results in loss of supporting bone. Disease management includes cleaning the surrounding flora by hand instruments, ultrasonic tips, las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
100
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 45 publications
(45 reference statements)
2
100
0
1
Order By: Relevance
“…Second, Ti particle-induced calvarial osteolysis model, as we used, under-represents the wear-debris-induced osteolysis model used in the emulation of aseptic prosthetic loosening pathogenesis. Different types of wear particles found in the bone-graft interface of patients with different implant materials such as Ti (Eger et al, 2018), cobalt-chromium-molybdenum (CoCrMo) , ceramics (Gibon et al, 2017), tricalcium phosphate (Lv et al, 2016), polyether-ether-ketone (Du et al, 2018), highly cross-linked polyethylene, and ultrahigh-molecular-weight polyethylene (Ormsby et al, 2019) demonstrate various traits in osteolysis. In addition, the limitations that 30 mg Ti particles was locally administrated at one time to produce calvarial osteolysis model was discussed by Liu et al (Liu et al, 2014) in one of his study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Ti particle-induced calvarial osteolysis model, as we used, under-represents the wear-debris-induced osteolysis model used in the emulation of aseptic prosthetic loosening pathogenesis. Different types of wear particles found in the bone-graft interface of patients with different implant materials such as Ti (Eger et al, 2018), cobalt-chromium-molybdenum (CoCrMo) , ceramics (Gibon et al, 2017), tricalcium phosphate (Lv et al, 2016), polyether-ether-ketone (Du et al, 2018), highly cross-linked polyethylene, and ultrahigh-molecular-weight polyethylene (Ormsby et al, 2019) demonstrate various traits in osteolysis. In addition, the limitations that 30 mg Ti particles was locally administrated at one time to produce calvarial osteolysis model was discussed by Liu et al (Liu et al, 2014) in one of his study.…”
Section: Discussionmentioning
confidence: 99%
“…24 A large number of studies have reported that M1-type macrophages were stimulated and induced by wear debris, which is generated from the surface of an implant prosthesis, and released proinflammatory cytokines, creating a proinflammatory microenvironment. 10,43,44 This proinflammatory microenvironment further activates the osteoclastic signalling pathways and promotes the recruitment and differentiation of osteoclast precursor cells. 8 In our study, following TiPs stimulation, the M1-specific marker CCR7 was significantly increased, Second, although the proinflammatory cytokines mainly released by macrophages and the consequent immune responses change the local immune status, various cells, including osteoblasts, fibroblasts and mesenchymal cells, may also release proinflammatory cytokines and participate in the process of wear particle-mediated osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported that deacylcynaropicrin inhibited RANKL-mediated osteoclast fusion by promoting M2-type macrophage polarization 24. A large number of studies have reported that M1-type macrophages were stimulated and induced by wear debris, which is generated from the surface of an implant prosthesis, and released proinflammatory cytokines, creating a proinflammatory microenvironment 10,43,44. This proinflammatory microenvironment further activates the osteoclastic signalling pathways and promotes the recruitment and differentiation of osteoclast precursor cells 8.…”
mentioning
confidence: 99%
“…As a result of rapid advances of the biomaterials science, reliable implants were considered to be most widely accepted operative procedure for treating damaged skeleton and diseased organs, such as various skeletal defects, tooth deficiency, joints replacements and et al Due to the routine use of implants, wear particles or debris can be observed from surfaces in relative friction between implants and physiological environment, surfaces between different component of implant, scaffolds for tissue engineering, or materials for drug delivering [1][2][3][4] . In particle disease, peri-implant osteolysis which is caused by wear particles remains the main complication for implant failure after the surgical [5][6][7][8] .…”
mentioning
confidence: 99%
“…In the last 20 years, titanium (Ti) has evolved into one of the most widely used material for implant, tissue engineering, material for drug delivery and composite biomaterials, considered its outstanding mechanical properties 1,[13][14][15][16][17] . Nevertheless, Ti implants have some inherent disadvantages.…”
mentioning
confidence: 99%